Cytokines Elevated in HIV Elite Controllers Reduce HIV Replication In Vitro and Modulate HIV Restriction Factor Expression - Jacobs, Evan S.; Keating, Sheila M.; Abdel-Mohsen, Mohamed; Gibb, Stuart L.; Heitman, John W.; Inglis, Heather C.; Martin, Jeffrey N.; Zhang, Jinbing; Kaidarova, Zhanna; Deng, Xutao; Wu, Shiquan; Anastos, Kathryn; et al. (Journal of virology, 2017)
A subset of HIV-infected individuals termed elite controllers (ECs) maintain CD4 + T cell counts and control viral replication in the absence of antiretroviral therapy (ART). Systemic cytokine responses may differentiate ECs from subjects with uncontrolled viral replication or from those who require ART to suppress viral replication. We measured 87 cytokines in four groups of women: 73 ECs, 42 with pharmacologically suppressed viremia (ART), 42 with uncontrolled viral replication (noncontrollers [NCs]), and 48 HIV-uninfected (NEG) subjects. Four cytokines were elevated in ECs but not NCs or ART subjects: CCL14, CCL21, CCL27, and XCL1. In addition, median stromal cell-derived factor-1 (SDF-1) levels were 43% higher in ECs than in NCs. The combination of the five cytokines suppressed R5 and X4 virus replication in resting CD4 + T cells, and individually SDF-1β, CCL14, and CCL27 suppressed R5 virus replication, while SDF-1β, CCL21, and CCL14 suppressed X4 virus replication. Functional studies revealed that the combination of the five cytokines upregulated CD69 and CCR5 and downregulated CXCR4 and CCR7 on CD4 + T cells. The CD69 and CXCR4 effects were driven by SDF-1, while CCL21 downregulated CCR7. The combination of the EC-associated cytokines induced expression of the anti-HIV host restriction factors IFITM1 and IFITM2 and suppressed expression of RNase L and SAMHD1. These results identify a set of cytokines that are elevated in ECs and define their effects on cellular activation, HIV coreceptor expression, and innate restriction factor expression. This cytokine pattern may be a signature characteristic of HIV-1 elite control, potentially important for HIV therapeutic and curative strategies. IMPORTANCE Approximately 1% of people infected with HIV control virus replication without taking antiviral medications. These subjects, termed elite controllers (ECs), are known to have stronger immune responses targeting HIV than the typical HIV-infected subject, but the exact mechanisms of how their immune responses control infection are not known. In this study, we identified five soluble immune signaling molecules (cytokines) in the blood that were higher in ECs than in subjects with typical chronic HIV infection. We demonstrated that these cytokines can activate CD4 + T cells, the target cells for HIV infection. Furthermore, these five EC-associated cytokines could change expression levels of intrinsic resistance factors, or molecules inside the target cell that fight HIV infection. This study is significant in that it identified cytokines elevated in subjects with a good immune response against HIV and defined potential mechanisms as to how these cytokines could induce resistance to the virus in target cells.